2019
DOI: 10.1002/cbic.201900280
|View full text |Cite
|
Sign up to set email alerts
|

Transient N4‐Acyl‐DNA Protection against Cleavage by Restriction Endonucleases

Abstract: A set of five N4‐acyl‐modified 2′‐deoxycytidine 5′‐triphosphates were incorporated into modified DNA by using phi29 DNA polymerase, and cleavage by selected restriction endonucleases was studied. Modified DNA containing N4‐acyl functional groups in either one or both strands of a DNA molecule was resistant to the majority of restriction enzymes tested, whereas modifications outside of the recognition sequences were well tolerated. The N4‐acylated cytidine derivatives were subjected to competitive nucleotide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…coli that lacks exonuclease activity (Klenow exo – ). Although N 4-acylated 2′-deoxycytidine derivatives are incorporated in DNA by polymerases, we sought to identify the oxime ester that provides a compromise between being a good DNA polymerase substrate and sufficient stability in water. , The latter was a concern due to the aforementioned instability of the methyl oxime ester ( 2a ) in our hands, and we assumed that larger alkyl groups would hinder hydrolysis to the hydroxyl amine (the desilylated form of 3 ). However, we anticipated that oxime esters containing smaller alkyl groups would be superior DNA-polymerase substrates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…coli that lacks exonuclease activity (Klenow exo – ). Although N 4-acylated 2′-deoxycytidine derivatives are incorporated in DNA by polymerases, we sought to identify the oxime ester that provides a compromise between being a good DNA polymerase substrate and sufficient stability in water. , The latter was a concern due to the aforementioned instability of the methyl oxime ester ( 2a ) in our hands, and we assumed that larger alkyl groups would hinder hydrolysis to the hydroxyl amine (the desilylated form of 3 ). However, we anticipated that oxime esters containing smaller alkyl groups would be superior DNA-polymerase substrates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Their goal was to better understand DNA-protein affinity requirements for the development of biological tools. [40][41][42][43][44][45][46] The Hocek research group has thoroughly evaluated the impact of major groove nucleobase modifications on REs, and a few examples are presented here. Macíčková-Cahová et al demonstrated that 5-modified cytosine with moieties such as alkyl, phenyl or 3-nitrophenyl were not recognized by any of the bacterial type II REs tested including Afel, EcoRI and PvuII.…”
Section: Probing Restriction Endonucleases With Modified Dntpsmentioning
confidence: 99%